Efficient estimation of semiparametric conditional moment models with possibly nonsmooth residuals - Xiaohong Chen; Demian Pouzo (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper considers semiparametric efficient estimation of conditional moment models with possibly nonsmooth residuals in unknown parametric components () and unknown functions (h) of endogenous variables. We show that: (1) the penalized sieve minimum distance(PSMD) estimator (ˆ,ˆh) can simultaneously achieve root-n asymptotic normality of ˆ and nonparametric optimal convergence rate of h, allowing for noncompact function parameter spaces; (2) a simple weighted bootstrap procedure consistently estimates the limiting distribution of the PSMD ˆ ; (3) the semiparametric efficiency bound formula of Ai and Chen (2003) remains valid for conditional models with nonsmooth residuals, and the optimally weighted PSMD estimator achieves the bound; (4) the centered, profiled optimally weighted PSMD criterion is asymptotically chi-square distributed. We illustrate our theories using a partially linear quantile instrumental variables (IV) regression, a Monte Carlo study, and an empirical estimation of the shape-invariant quantile IV Engel curves.
Keywords: C14; C22; 330; Penalized sieve minimum distance; Nonsmooth generalized residuals; Nonlinear nonparametric endogeneity; Weighted bootstrap; Semiparametric efficiency; Confidence region; Partially linear quantile IV regression; Shape-invariant quantile IV Engel curves; Nichtparametrisches Verfahren; Bootstrap-Verfahren; Schätztheorie